Personal Branding Ira Mirawati sebagai Content Creator Edukasi di TikTok - Nadhira, Ziyan; Rahmat, Agus; Setianti, Yanti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
In the digital era, individuals must establish a strong personal brand image, particularly on social media platforms. This study focuses on analyzing the personal branding of Ira Mirawati as an educational content creator on TikTok. The research method used is qualitative research with descriptive studies. The result stated that Ira Mirawati effectively utilizes TikTok to showcase her skills, values, principles, and characteristics. Ira Mirawati has the ability as an educational practitioner who knows deeply about lectures. Ira Mirawati consistently shares education by developing her skills. In addition, the characteristics of Ira Mirawati are humble, friendly, and humorous. So, the combination of several aspects can create the uniqueness of Ira Mirawati.